Perineal colostomy with spiral smooth muscle graft for neosphincter reconstruction following abdominoperineal resection of very low Rectal cancer: long-term outcome - Hirche, Christoph; Mrak, Karl; Kneif, Sören; Mohr, Zarah; Slisow, Wasilij; Hünerbein, Michael; Gretschel, Stephan (Diseases of the colon & rectum, 2010)
BACKGROUND: - To avoid abdominal colostomy and improve quality of life, several types of anorectal reconstruction following abdominoperineal resection have been proposed. The aim of this study was to assess functional results and the quality of life of patients with very low rectal cancer after abdominoperineal resection and neosphincter reconstruction by perineal colostomy with a colonic muscular cuff. - PATIENTS AND METHODS: - Twenty-seven patients who had undergone neosphincter reconstruction with a perineal spiral cuff plasty after abdominoperineal resection were included in a retrospective study to evaluate long-term outcome. The functional results were analyzed using anal manometry and the continence score. The quality of life was measured with the global and disease-specific questionnaires European Organization for Research and Treatment of Cancer QLQ-C30 and C38. - RESULTS: - Median follow-up time was 105 months (range, 18-185 mo). The median Holschneider continence score of the study sample was 13 (continent), with a range of 10 (partially continent) to 16 (continent), thus demonstrating satisfactory functional results. The functional assessment was completed by neosphincter manometry which revealed a median resting vs compression pressure of 40 vs 96 cmH2O with a range of 5 to 81 cmH2O vs 49 to 364 cmH2O. The quality-of-life analyses showed an above-average score for both global health and disease-specific status. - CONCLUSION: - Spiral cuff colostomy with reconstruction after abdominoperineal resection of very low distal rectal cancer offers a surgical option for a selective group of patients with reasonable functional long-term results and an improved quality of life.
Gesehen am 15.05.2023